Interaction of Organisms in Abandoned Tin Mining Pits: Perspective of Life in Acid Mine Drainage Environment - Andri Kurniawan; Ardiansyah Kurniawan; Robin Robin (School of Postgraduate Studies, Diponegoro Univer, 2023)
Acid Mine Drainage (AMD) occured after mining activity exposes metal sulphides to oxidizing conditions that impact acidic condition with low pH value in the waters and heavy metals contamination. These conditions are also occurred in abandoned tin mining pits, one of placed in Bangka Belitung Archipelago Province. This mini review aimed to elaborate information of micro- and macro-organism’ life in acid mine drainage to be associated with the possibility of life in abandoned tin mining pits. Acidophilic and acidotolerant organisms such as bacterial, phyto- and zooplankton, and some macroorganism included invertebrate or vertebrate like fishes and also water plants were found in these waters. Their presence developed a symbiosis interaction in aquatic environment. Phytoplankton is an autotroph organism, despite being considered autotroph organism, many phytoplankton require exogenous organic cofactors and nutrients for their life. These cofactors were often served by heterotroph bacterial to sustain the growth of phytoplankton. Instead, bacterial obtained dissolved organic matter derived from phytoplankton to survive in the aquatic environment. Furthermore, phytoplankton was consumed by zooplankton; zooplankton was consumed by small fish to big fish in the waters. In addition, water plants also support the interaction of organisms in the water by supplying dissolved oxygen, also anorganic and organic material for their life. The symbiosis and quorum sensing plays an important role in structuring the aquatic food web and creating a life in the acidic water-polluted heavy metal.